PENGARUH PELATIHAN, INTEGRITAS, DAN EFIKASI DIRI TERHADAP EFEKTIVITAS MANAJERIAL KEPALA SEKOLAH DASAR NEGERI DI PROVINSI DKI JAKARTA - HARYANTO, HARYANTO (PPs UNJ, 2016)
This research aims to analyze the impact of training, integrity, and self eficacy on the managerial effectiveness of the head of state primary school of Jakarta Provincial Education Office. The survey was conducted in this study with 75 samples of state primary school with random sampling technique. The data were processed with path analysis. The results showed that: (1) training effects positive directly on the managerial effectiveness. (2) Integrity effects positive directly on the managerial effectiveness. (3) Self Eficacy effects positive directly on the managerial effectiveness. (4) Training effects positive directly on Self-efficacy. (5) Integrity effects positive directly on Self-efficacy. (6) Training effects positive directly on Integrity. Based on the findings it can be concluded that in order to improve the managerial effectiveness, it should be increased the teacher’s training, integrity, and Self-efficacy. And to improve the Self-efficacy, it should be increased the teasher’s training and integrity.